A nonS-locus F-box gene breaks self-incompatibility in diploid potatoes - Ling Ma (Nature Portfolio, 2021)
Diploid potatoes are typically self-incompatible, complicating efforts to breed diploid cultivars. Here the authors report map-based cloning of the S-locus inhibitor (Sli) gene in potato which encodes a non S-locus F-box protein that is expressed in pollen and can functions like a general S-RNase inhibitor to overcome self-incompatibility.